(3EOGQI GdCYeGd GdOhdjIs - (3eMehO LGSe(B, (3GdUejOYjs; (3QOjfI(B, (3YKeGf jhSas ((3YeGf(B:s (3OGQ GdefGgL ddfTQ(B,s, 2007)
(3jVe ebOeI aj EOGQI GdGYeGd GdOhdjI h HjFI GdGYeGd GdOhdjI, fXQjGJ GdGYeGd GdOhdjI , GdefGaSI GdchfjI h JMdjd h GNJHGQ GdGShGb GdOhdjI, gjcd GdGYeGd GdchfjI GdJShjb GdOhdj, GdJYbjOGJ GdGVGajI ddJShb GdOhdj, GOGQI GdGfJGL GdOhdj h fXGe GdGeOGO,GOGQI GdehGQO GdHTQjI, GdGOGQI GdeGdjI GdOhdjI(B. s
(3HjHdjhZQGajG(B: (3U(B.311-317s
Keywords: (3EOGQI GdCYeGds; (3GdJShjb GdOhdjs